High-temperature quantum coherence of spinons in a rare-earth spin chain - Lazar L. Kish; Andreas Weichselbaum; Daniel M. Pajerowski; Andrei T. Savici; Andrey Podlesnyak; Leonid Vasylechko; Alexei Tsvelik; Robert Konik; Igor A. Zaliznyak (Nature Communications)
Abstract Conventional wisdom dictates that quantum effects become unimportant at high temperatures. In magnets, when the thermal energy exceeds interactions between atomic magnetic moments, the moments are usually uncorrelated, and classical paramagnetic behavior is observed. This thermal decoherence of quantum spin behaviors is a major hindrance to quantum information applications of spin systems. Remarkably, our neutron scattering experiments on Yb chains in an insulating perovskite crystal defy these conventional expectations. We find a sharply defined spectrum of spinons, fractional quantum excitations of spin-1/2 chains, to persist to temperatures much higher than the scale of the interactions between Yb magnetic moments. The observed sharpness of the spinon continuum’s dispersive upper boundary indicates a spinon mean free path exceeding  ≈ 35 inter-atomic spacings at temperatures more than an order of magnitude above the interaction energy scale. We thus discover an important and highly unique quantum behavior, which expands the realm of quantumness to high temperatures where entropy-governed classical behaviors were previously believed to dominate. Our results have profound implications for spin systems in quantum information applications operating at finite temperatures and motivate new developments in quantum metrology.